Kecanggihan Smartphone sebagai Media Pembelajaran Di Era Modern - Azizah, Nur Afni; Hutami, Ahmad; Norlita, Norlita (Borneo Journal of Islamic Education, 2023)
Abstract The sophistication of features on smartphones is increasing and can be used for learning purposes. However, it still needs to be explored the extent of its potential use. Therefore, this study aims to identify and analyze the ways how. The sophistication of smartphones can be used as learning media in the modern era. The research method used is a qualitative research method with a descriptive literature review technique. The results of the analysis show that smartphones have great potential in supporting learning in the modern era. The sophistication of smartphones in terms of features, internet connection, and multimedia capabilities, allows users to access various information and learning resources available in cyberspace. In addition, learning applications available on smartphones also allow users to study independently and flexibly, anytime and anywhere. However, the use of smartphones as learning media also has challenges and risks that need to be considered, such as the risk of dependence and impaired concentration. In this study, the authors recommend that the use of smartphones as learning media in the modern era needs to be balanced with supervision and assistance from educators or parents. In addition, it is also necessary to develop more innovative and interactive learning applications that can maximize the sophistication potential of smartphones as learning media. Keywords: Smartphone, Media Pembelajaran, Era Modern. Abstrak Kecanggihan fitur pada smartphone semakin banyak dan dapat dimanfaatkan untuk keperluan pembelajaran. Namun, masih perlu dieksplorasi sejauh mana potensi penggunaannya. Oleh karena itu, penelitian ini bertujuan untuk mengidentifikasi dan menganalisis cara-cara bagaimana. kecanggihan smartphone dapat dimanfaatkan sebagai media pembelajaran di era modern. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan teknik literatur review deskriptif. Hasil analisis menunjukkan bahwa smartphone memiliki potensi yang besar dalam mendukung pembelajaran di era modern. Kecanggihan smartphone dalam hal fitur, koneksi internet, dan kemampuan multimedia, memungkinkan pengguna untuk mengakses berbagai informasi dan sumber pembelajaran yang tersedia di dunia maya. Selain itu, aplikasi pembelajaran yang tersedia di smartphone juga memungkinkan pengguna untuk belajar secara mandiri dan fleksibel, kapan saja dan di mana saja. Namun, penggunaan smartphone sebagai media pembelajaran juga memiliki tantangan dan risiko yang perlu diperhatikan, seperti risiko ketergantungan dan gangguan konsentrasi. Dalam penelitian ini, penulis merekomendasikan agar penggunaan smartphone sebagai media pembelajaran di era modern perlu diimbangi dengan pengawasan dan pendampingan dari pendidik atau orang tua. Selain itu, perlu juga dikembangkan aplikasi pembelajaran yang lebih inovatif dan interaktif yang dapat memaksimalkan potensi kecanggihan smartphone sebagai media pembelajaran. Kata kunci: Smartphone, Media Pembelajaran, Era Modern